Distinct glycoconjugate cell surface structures make the pelagic diatom Thalassiosira rotula an attractive habitat for bacteria - Den, Tran Quoc (Journal of phycology, 2023)
© 2022 The Authors. Journal of Phycology published by Wiley Periodicals LLC on behalf of Phycological Society of America.